Manejo agronómico del cultivo de pitahaya (Hylocereus undatus) roja, en Ecuador - Silva Veas, Jeniffer Gabriela (2022)
This work deals with the agronomic management of the red pitahaya (Hylocereus undatus) crop in Ecuador. Today there are several producers and farmers who are dedicated to its development, but many of them do not have sufficient information and knowledge to be able to bring said fruit to its highest production, causing low profitability, sustainability and at the same time a waste of resources. agrochemicals empirically causing indirect contamination to the environment altering both the fauna of beneficial insects and the microfauna found in the soil to work. In the present, information of all kinds will be detailed, which will be compiled from various sources such as research links, magazines, scientific articles, forums, books, interviews, among others, which will explain what the appropriate tasks are during the entire cultivation process from its germination. until harvest time. The importance of it within the country will also be discussed, since today this fruit has been placed as an export crop of great importance both economically and for its wide beneficial use for health due to a number of qualities that make it This fruit is one of the most important in the daily diet of every person. Culminating in this way, it will be known how benefactor is the cultivation of red pitahaya (Hylocereus undatus) within the country. Keywords: red pitahaya, hylocereus undatus, benefits, agronomic management, export.